Teleconference Marriage Contracts and The Development of Indonesian Marriage Law - Miftahul Qodril R; Ishaq Ishaq; Pujiono Pujiono (Indonesian Journal of Law and Islamic Law (IJLIL), 2022)
In the current era of technology, it is possible to carry out a marriage contract with the help of technology that can facilitate the parties who will carry out the marriage contract. In the study of Islamic law, there is no definite law regarding this long-distance marriage. Because this is a case of ijtihadiyah which is not mentioned in the texts of the Qur'an or Sunnah. In Indonesia, there is also no legal certainty regarding long-distance marriage contracts. This study uses library research method where literature is the main data source. This study aims to determine the views of an Islamic figure regarding the marriage contract carried out by teleconference, as well as to find out the prospects for this view in the development of Islamic family law in Indonesia. The results of this study indicate that the marriage contract through teleconferencing is factually not yet regulated in marriage law. However, according to Wahbah Az-Zuhaili's opinion, marriage via teleconference is a marriage that is allowed and can be considered valid. However, it is still necessary to regulate and amend the law regarding teleconferencing marriage contracts in order to protect the law, as well as to fulfill the legal aspect for the parties concerned.